2023
DOI: 10.1039/d2cp03489a
|View full text |Cite
|
Sign up to set email alerts
|

Plasma activated water: a study of gas type, electrode material, and power supply selection and the impact on the final frontier

Abstract: An in-depth study of plasma activated water (PAW) generation was conducted to link changes in power supply, electrode material, input gas, and treatment time to the resulting reaction chemistry. These...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…Improving the generation efficiency of PAW to ensure the production and absorption of more active particles in a shorter time is a key issue. Previous studies have shown that various factors, such as electrode configuration, plasma treatment time, applied voltage, gas environment, solution composition and volume, as well as treatment method, have significant impacts on the generation of RONS and the physicochemical properties (pH and conductivity) of PAW [15,22,44,45]. By combining with plasma bubbling technology, it is possible to further improve the energy efficiency in our system.…”
Section: Discussionmentioning
confidence: 99%
“…Improving the generation efficiency of PAW to ensure the production and absorption of more active particles in a shorter time is a key issue. Previous studies have shown that various factors, such as electrode configuration, plasma treatment time, applied voltage, gas environment, solution composition and volume, as well as treatment method, have significant impacts on the generation of RONS and the physicochemical properties (pH and conductivity) of PAW [15,22,44,45]. By combining with plasma bubbling technology, it is possible to further improve the energy efficiency in our system.…”
Section: Discussionmentioning
confidence: 99%
“…This novel approach involves subjecting water to non-thermal plasma exposing it to ROS and RNS [5] and inducing changes in the physicochemical properties of the liquid. These changes can be tailored for different applications [6,7]. Reactive species in PAW impart beneficial effects on plants inducing physiological and biochemical changes with positive effects on growth and stress tolerance [6].…”
Section: Introductionmentioning
confidence: 99%
“…The ability of plasma-liquid interactions to generate a rich variety of reactive species is now widely recognized, offering remarkable biochemical activity to the liquid in contact with the plasma. [1][2][3][4] Numerous attractive and promising applications are being developed in the fields of biomedicine, environmental governance and chemical synthesis. [5][6][7][8] Diverse forms of plasma-liquid interactions have been established for scientific research and applications, where gas-liquid discharge is easily achievable and efficient in generating reactive oxygen and nitrogen species (RONS).…”
Section: Introductionmentioning
confidence: 99%